Treatment of Oilfield Produced Water Using Three Electrochemical Processes: Comparative Study - Al-Ameri, Wahbi; Elhassan, Ahmed; Maher, Ragaei (University of Khartoum Engineering Journal, 2022)
Although various techniques exist for remediation of wastewater, electrochemical technology and electrochemical advanced oxidation processes are the most promising and innovating methods for destroying and eliminating a broad-range of organic and inorganic contaminants presented in the produced water effluents. This study presents integrated electrochemical treatment techniques including electrocoagulation process, electrooxidation process and electro-Fenton process for a real produced water, supplied by an oil company. The electrocoagulation method was conducted by iron and aluminum electrodes, electrooxidation method by graphite electrodes and the electro-Fenton method by iron and graphite electrodes. The experiments were performed in the same electrolytic batch cell with the same spacing between electrodes and electrode surface. The feasibility of treatment processes was monitored by the removal of total organic carbon (TOC) and chemical oxygen demand (COD).As a result of the study, the most efficient technology was the electrooxidation process where the removal efficiencies of TOC and COD were 93.5 % and 94 %, respectively. Additionally, electro-Fenton process led to higher removal efficiencies reaching 85 % and 87 % for TOC and COD, respectively. The electrocoagulation treatment of produced water by using iron and aluminum electrodes was moderately efficient for removal of TOC. However, it was inefficient for removal of COD. Furthermore, electrocoagulation remediation was proved to be an effective method for removal of inorganic species such as calcium, magnesium and sulfate. It can be concluded that electrochemical methods could be used for effective produced water treatment where it can be safely disposed of or effectively reused for injection and irrigation.